Postpartum nursing consultation in primary care: scientific evidence (Research, Society and Development, 2022)
Objective: to identify the national and international scientific evidences concerning available tools for postpartum consultation in primary care. Method: consists of a study performed through an integrative review of the literature in the following data bases: BDENF; LILACS; MEDLINE e SCIELO. In the study 13 articles were included, the analysis was conducted through an evaluative matrix which considers the characterization of the study, an answer to a research question and level of evidence. Results: after a pré-analysis, material exploration and interpretation, 2 categories that allowed to synthesize the findings were originated: tools used to mediate the postpartum nursing consultation and technological nursing strategies for postpartum health education. Conclusion: the findings of this study point to several tools and technological strategies used to perform the nursing consultation in the period of the pregnancy-puerperal cycle. It is believed that by promoting the use, creation and improvement of these activities, it is possible to optimize, qualify and individualize the care.